2006
DOI: 10.1007/s11095-006-9153-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Film Thickness on Thermal Aerosol Generation

Abstract: Rapid vaporization of pharmaceuticals coated as thin films on substrates is an efficient way of generating drug aerosols. By controlling the film thickness, the amount of aerosol decomposition can be minimized to produce high purity aerosols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The effect of temperature 77 , initial film thickness 78 and energy 79 on the condensation aerosol was previously studied. The method was successfully used to make ibuprofen and indomethacin nanoparticles for inhalation 80,81 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The effect of temperature 77 , initial film thickness 78 and energy 79 on the condensation aerosol was previously studied. The method was successfully used to make ibuprofen and indomethacin nanoparticles for inhalation 80,81 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Vaporized drug resublimates into distinct aerosolized particles within a respirable size range, to be subsequently entrained by the airflow. Size distribution of the resublimated particles is controlled by the airflow velocity over the vaporizing compound (96). Even though the device locally generates high temperatures, it was shown that the peak wet bulb temperature of the outlet stream of 39.9 ±0.1°C, determined in a worst-case scenario setup, is well below the recommended standard of 50°C (97).…”
Section: Staccatomentioning
confidence: 99%
“…7 In brief, loxapine was solubilized in an organic solvent and spray coated onto stainless steel foils. The solvent was allowed to evaporate to form a crystalline coating of loxapine.…”
Section: Loxapine Coatingmentioning
confidence: 99%